Epigenetic and gene regulatory functions of small RNAs - Cecere, Germano (Comptes Rendus Biologies)
In this review article, I summarize the intervention I made during the “Hommage à François Gros” held at the Institut Pasteur in Paris on the 25th of April, 2023. I discuss how the discovery of the existence of an RNA intermediate between genetic information and protein translation has changed our perspective on the role of RNA in gene regulation in these past years. I also discuss new emerging paradigms, highlighting the role of RNA in heritable information similar to the well-known DNA function.